High enhancer activity is an epigenetic feature of HPV negative atypical head and neck squamous cell carcinoma - Callahan, S. Carson; Kochat, Veena; Liu, Zhiyi; Raman, Ayush T.; Divenko, Margarita; Schulz, Jonathan; Terranova, Christopher J.; Ghosh, Archit K.; Tang, Ming; Johnson, Faye M.; Wang, Jing; Skinner, Heath D; et al. (Frontiers in Cell and Developmental Biology, 2022)
Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous disease with significant mortality and frequent recurrence. Prior efforts to transcriptionally classify HNSCC into groups of varying prognosis have identified four accepted molecular subtypes of disease: Atypical (AT), Basal (BA), Classical (CL), and Mesenchymal (MS). Here, we investigate the active enhancer landscapes of these subtypes using representative HNSCC cell lines and identify samples belonging to the AT subtype as having increased enhancer activity compared to the other 3 HNSCC subtypes. Cell lines belonging to the AT subtype are more resistant to enhancer-blocking bromodomain inhibitors (BETi). Examination of nascent transcripts reveals that both AT TCGA tumors and cell lines express higher levels of eRNA transcripts for enhancers controlling BETi resistance pathways, such as lipid metabolism and MAPK signaling. Additionally, investigation of higher-order chromatin structure suggests more enhancer-promoter (E-P) contacts in the AT subtype, including on genes identified in the eRNA analysis. Consistently, known BETi resistance pathways are upregulated upon exposure to these inhibitors. Together, our results identify that the AT subtype of HNSCC is associated with high enhancer activity, resistance to enhancer blockade, and increased signaling through pathways that could serve as future targets for sensitizing HNSCC to BET inhibition.